2018
DOI: 10.3389/fmicb.2018.01571
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Non-biodegradable and Biodegradable Plastics by Marine Microorganisms

Abstract: Plastics are ubiquitous in the oceans and constitute suitable matrices for bacterial attachment and growth. Understanding biofouling mechanisms is a key issue to assessing the ecological impacts and fate of plastics in marine environment. In this study, we investigated the different steps of plastic colonization of polyolefin-based plastics, on the first one hand, including conventional low-density polyethylene (PE), additivated PE with pro-oxidant (OXO), and artificially aged OXO (AA-OXO); and of a polyester,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
178
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(202 citation statements)
references
References 79 publications
18
178
3
3
Order By: Relevance
“…Using aquaria filled with natural circulating seawater, Dussud et al [105] detected over 6 weeks the marine microorganisms associated with the successive phases of colonization, growing, and maturation of the biofilms developing on non-biodegradable [i.e., polyolefins such low-density PE, PE additivated with pro-oxidant (OXO)] compared to biodegradable polymers [i.e., artificially aged OXO (AA-OXO) and a polyester, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)]. All these substrates showed variable surface properties in terms of hydrophobicity and roughness.…”
Section: Mixed Substratesmentioning
confidence: 99%
“…Using aquaria filled with natural circulating seawater, Dussud et al [105] detected over 6 weeks the marine microorganisms associated with the successive phases of colonization, growing, and maturation of the biofilms developing on non-biodegradable [i.e., polyolefins such low-density PE, PE additivated with pro-oxidant (OXO)] compared to biodegradable polymers [i.e., artificially aged OXO (AA-OXO) and a polyester, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)]. All these substrates showed variable surface properties in terms of hydrophobicity and roughness.…”
Section: Mixed Substratesmentioning
confidence: 99%
“…This study showed that all the tested bacteria adhered to polystyrene, 90% were moderately and strongly adherent. Many studies indicate that surface roughness influences bacteria adhesion (Lorite et al, 2011;Dussud et al, 2018). Baker and Greenham (1988) found that roughening the surface of either glass or polystyrene with a grindstone greatly increased the rate of bacterial colonization.…”
Section: /10mentioning
confidence: 99%
“…The functional groups that form on the surface of plastic during abiotic degradation (keto carbonyls, esters, vinyls and double bonds) (Restrepo-Flórez et al 2014) also change the hydrophobicity of the plastic surface (Fotopoulou and Karapanagioti 2015). The balance between the production and microbial consumption of these functional groups also affects the hydrophobicity of the plastic as degradation continues (Dussud et al 2018a).…”
Section: Evidence Of Plastic Biodegradationmentioning
confidence: 99%